Bauchlagerung bei Beatmung – Schritt für Schritt - Vogt, Tobias Bertram; Sensen, Barbara; Kluge, Stefan (DMW - Deutsche Medizinische Wochenschrift, 2019)
The Acute Respiratory Distress Syndrome is still a very severe condition in intensive care patients. Prone positioning is known to improve outcome in patients with moderate to severe ARDS. Therefore proning in these patients is nowadays to be regarded as a standard of care. The risks of proning are reasonably low – if proning is done correctly. Therefore a method of proning in a step-by-step-approach is shown in this article.
Keywords: ARDS; Bauchlagerung; mechanische Beatmung